2009
DOI: 10.1038/onc.2008.497
|View full text |Cite
|
Sign up to set email alerts
|

Ha-Ras transformation of MCF10A cells leads to repression of Singleminded-2s through NOTCH and C/EBPβ

Abstract: We have previously shown that Singleminded-2s (SIM2s), a member of the basic helix-loop-helix Per-Arnt-Sim (bHLH/ PAS) family of transcription factors, is downregulated in breast cancer samples and has tumor suppressor activity. However, the mechanism by which SIM2s is repressed in breast cancer cells has not been determined. In this study, we show that transformation of MCF10A cells by HarveyRas (Ha-Ras) induces CCAAT/enhance binding protein b (C/EBPb) and activates the NOTCH signaling pathway to block SIM2s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 37 publications
(49 reference statements)
1
30
0
Order By: Relevance
“…Furthermore, reestablishment of Sim2s in highly invasive cancer cells significantly inhibits growth and motility, suggesting that Sim2s is a breast tumor suppressor (Kwak et al, 2007). In addition, we found that SIM2s expression is suppressed by NOTCH and CEBPb and that loss of SIM2s in normal human breast and mouse mammary epithelium induces an invasive basal/stem cell-like phenotype (Gustafson et al, 2009;Laffin et al, 2008). Sim2s-null mouse mammary glands do not undergo proper ductal elongation or luminal differentiation (Laffin et al, 2008).…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Furthermore, reestablishment of Sim2s in highly invasive cancer cells significantly inhibits growth and motility, suggesting that Sim2s is a breast tumor suppressor (Kwak et al, 2007). In addition, we found that SIM2s expression is suppressed by NOTCH and CEBPb and that loss of SIM2s in normal human breast and mouse mammary epithelium induces an invasive basal/stem cell-like phenotype (Gustafson et al, 2009;Laffin et al, 2008). Sim2s-null mouse mammary glands do not undergo proper ductal elongation or luminal differentiation (Laffin et al, 2008).…”
Section: Introductionmentioning
confidence: 63%
“…We have previously shown that SIM2s is expressed in human breast luminal epithelial cells and loss of SIM2s in normal human breast cell lines and mouse mammary epithelium during virgin development induces an invasive basal/stem cell-like phenotype (Laffin et al, 2008;Gustafson et al, 2009). To further evaluate the role of Sim2s in mammary gland development, we provide new data demonstrating that Sim2s is upregulated in a stepwise manner during early lactation, similar to that of Csn2 and Wap, but not Lalba and Expi.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Zhu et al demonstrated that C/EBPβ-null mice are completely refractory to skin tumor formation induced by a variety of carcinogens which produce tumors containing oncogenic Ras mutations, and that C/EBPβ participated in Ras-induced transformation of NIH 3T3 fibroblasts (16). In Ras-transformed MCF10A cells, C/EBPβ suppressed expression of tumor suppressor Sigleminded-2, which has been found to inhibit malignant transformation of mammary ductal cells (19). Thus, C/ EBPβ is downstream of the Ras signaling pathway and is required for Ras-induced malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPβ belongs to a basic-leucine zipper transcription factor family and plays multiple roles in the control of inflammation, cellular proliferation, survival and differentiation, and tumorigenesis (14)(15)(16)(17). Recent evidence indicates that C/EBPβ is critical for carcinogen-and oncogene-mediated cell transformation (18,19). Furthermore, C/EBPβ activation is indispensable to liver proliferation and fibrosis (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%